2021
DOI: 10.1016/j.carbon.2020.08.065
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined sub-nanometer graphene ribbons synthesized inside carbon nanotubes

Abstract: Graphene nanoribbons with sub-nanometer widths are extremely interesting for nanoscale electronics and devices as they combine the unusual transport properties of graphene with the opening of a band gap due to quantum confinement in the lateral dimension. Strong research efforts are presently paid to grow such nanoribbons. Here we show the synthesis of 6-and 7-armchair graphene nanoribbons, with widths of 0.61 and 0.74 nm, and excitonic gaps of 1.83 and 2.18 eV, by high-temperature vacuum annealing of ferrocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
(104 reference statements)
3
33
0
Order By: Relevance
“…In previous works, hydrogen-terminated GNRs formed inside of the SWCNTs were successfully imaged by HR-TEM, despite the electron beam damage. 29 In the case of sulfur terminated or chlorine terminated NRs, the edges of the encapsulated structures are more stable and can be resolved clearly in a zigzag configuration. 32,33 However, even when the exact atomic structure of the nanoribbon edge is not possible to be resolved by HR-TEM, the key structural characteristic is the helical twist, a result of nanoribbon confinement inside the nanotube, that allows distinguishing NRs from the encapsu-lated molecules or internal nanotubes.…”
Section: Copcnr Structurementioning
confidence: 99%
See 2 more Smart Citations
“…In previous works, hydrogen-terminated GNRs formed inside of the SWCNTs were successfully imaged by HR-TEM, despite the electron beam damage. 29 In the case of sulfur terminated or chlorine terminated NRs, the edges of the encapsulated structures are more stable and can be resolved clearly in a zigzag configuration. 32,33 However, even when the exact atomic structure of the nanoribbon edge is not possible to be resolved by HR-TEM, the key structural characteristic is the helical twist, a result of nanoribbon confinement inside the nanotube, that allows distinguishing NRs from the encapsu-lated molecules or internal nanotubes.…”
Section: Copcnr Structurementioning
confidence: 99%
“…In addition to the bottom-up approach 26,27 that is limited to the onsurface synthesis and to only specific precursors that can be used, GNRs can be specifically formed inside the nanotubes. Growth inside the nanotube channels is advantageous since various molecules can be used including fullerenes, 28 PAH, 17 and ferrocenes, 29 resulting in the formation of long and narrow GNRs with various geometries. Recent experiments combining transmission electron microscopy and multi-wavelength Raman spectroscopy unambiguously prove the formation of highly uniform GNRs with identical properties inside the nanotubes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that by carefully controlling the starting SWCNT diameters and the exact annealing temperature, 6-and 7 armchair graphene nanoribbons (6-and 7-AGNRs) with well-defined structure were grown inside SWCNTs, and their electronic and vibrational properties were characterized in detail by wavelength-dependent Raman scattering spectroscopy (Figure 6d). [108] The Raman spectra show the features of the surrounding SWCNTs (RBMs, D and G-bands), those of newly synthesized inner tubes in the RBM region (highlighted by the circle in Figure 6d) and the distinctive radial-breathing-like-modes (RBLM) and higher-frequency modes of the encapsulated armchair graphene nanoribbons (AGNRs) (highlighted by the squared boxes in Figure 6d). Interestingly, the synthesis of GNRs inside SWCNTs can be achieved both from functionalized fullerenes, polycyclic aromatic hydrocarbons, and ferrocene, thus showing that mainly carbonrich precursors are needed combined with other atoms (H, O, N, S, …) to terminate the edges.…”
Section: Transformation Of Precursor Molecules Inside Swcntsmentioning
confidence: 99%
“…The right panels present a selection of the electronic resonance profiles for the D-modes of the AGNRs, plotting Raman intensity as a function of excitation energy, directly yielding information on the electronic structure of the AGNRs. Adapted with permission [108]. Copyright 2021, Elsevier.…”
mentioning
confidence: 99%